Incidencia de la organización social juvenil manos negras en el desarrollo sociocultural de la ciudad de Machala 2013 - Suárez Quishpe, Juan Carlos (2016)
The present scientific research provides the necessary information to verify if the activism of the youth organization Manos Negras has an effecting the socio-cultural development of the city of Machala. Said organization in turn unites five youth organizations in the city.